Development and Validation of a Literacy Acquisition Factors Instrument for Grades 1–3 Learners - Rosebell Tungol; Rene Boy Abiva (Research Synergy Foundation, 2026)
Early literacy acquisition is a critical foundation for academic success, yet many Grades 1–3 learners experience reading and comprehension difficulties without the support of validated diagnostic tools that identify both enabling and hindering factors within their learning context. Existing school-based literacy programs often rely on general assessments that do not systematically capture socio-cultural, motivational, and environmental influences affecting literacy development. This study developed and validated a diagnostic instrument designed to identify success and barrier factors influencing literacy acquisition in English and Filipino among primary learners. Anchored in the Alalay sa Literasiya initiative of the Community Extension and Outreach Project Office (CEOPO) at Manuel V. Gallego Foundation Colleges (MVGFC), the tool supports targeted, evidence-based classroom and intervention planning. The instrument measures success indicators (e.g., reading interest, self- awareness, language exposure, and socio-cultural support) and barrier indicators (e.g., family constraints, financial limitations, environmental factors, and motivation) using a 4-point Likert scale, including a Filipino- language version to ensure accessibility. Face and content validation were conducted by literacy and education experts. Quantitative validation using the Content Validity Ratio (CVR) and Content Validity Index (CVI) yielded a high scale-level CVI (S-CVI = 0.935), while reliability testing showed excellent internal consistency (Cronbach’s alpha = 0.930). These findings confirm that the instrument is valid and reliable for identifying literacy-related factors and can assist teachers and schools in designing responsive literacy interventions for Grades 1–3 learners.